Intravenous cyclophosphamide and immunoglobulin ameliorated visual field defects in a patient with eosinophilic granulomatosis with polyangiitis - Yuto Motobayashi; Chiyako Oshikata; Yuka Kodama; Kosuke Terada; Yuga Yamashita; Ryo Nakadegawa; Hinako Masumitsu; Reeko Osada; Hirokazu Takayasu; Nami Masumoto; Saki Manabe; Takeshi Kaneko; et al. (Respiratory Medicine Case Reports, 2024)
Treating ocular involvement in eosinophilic granulomatosis with polyangiitis (EGPA) can be challenging. We present the case of a 37-year-old woman with EGPA who had severe bilateral visual field defects. Laboratory results showed leukocytosis (17,500 WBC/μL, 25.8 % eosinophils), negative MPO-ANCA titer, and elevated PR3-ANCA level (33.2 IU/mL). Diffusion-weighted MRI revealed bilateral hyperintense occipital lesions, which were more prominent on the left. Her therapy initially included a steroid pulse, followed by daily prednisolone, but her visual field defects remained refractory. The addition of intravenous cyclophosphamide (5 courses) and intravenous immunoglobulin decreased her optic neuropathy and resolved her visual field defects.